Benign Paroxysmal Positional Vertigo (BPPV) - Firdiansari, Alifia (Jurnal Syntax Fusion, 2022)
BPPV is a condition of disturbance of the peripheral vestibular system, when the patient feels the sensation of spinning and moving associated with nystagmus when the head position changes against gravity and is accompanied by symptoms of nausea, vomiting and cold sweats. The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were carried out on online portals for journal publications such as MedScape Google Scholar (scholar.google.com) and the National Centre for Biotechnology Information/NCBI (ncbi.nlm.nih.gov), with the keyword ‘Benign paroxysmal positional vertigo (BPPV)”. BPPV is characterized by sudden, brief episodes of vertigo triggered by certain head movements that usually result from displacement of calcium-carbonate crystals or otoconia within the fluid-filled semicircular canals of the inner ear. The diagnosis of BPPV can be made based on anamnesis and physical examination which includes several tests, including the Dix-Hallpike. The diagnosis of BPPV can be made through clinical history along with diagnostic procedures. The management that is often used is non-pharmacological which includes several maneuvers such as the Epley maneuver, the Semount maneuver and the Lempert maneuver